Diabetes as a Risk Factor of Pancreatic Cancer - Muhammad Asif, Syed Whaj Ahmad, Syed Faraz Ahmad, Ahmed Nawaz Banu, Maheen Jamil, Nahal Arshad, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to determine the relation between diabetes and pancreatic cancer. Study Design: Retrospective study Place and Duration: Tehsil Headquarter Hospital Minchinabad. May 2021-Dec 2021 Methods: There were two hundred and fifty patients of pancreatic cancer were included in this study. Age of the patients was between 20-90 years. Informed written consent was taken from all the patients for detailed demographics age, sex, body, mass index. Patients were underwent for CT scan and ultrasonography. Outcomes were association of diabetes among enrolled cases was measured. Age duration of diabetes among all the cases were measured. Prevalence of cancer among different regions of pancreas was studied. SPSS 24.0 version was used to analyze complete data. Results: There were 160 (64%) males and 90 (36%) cases were females. Mean age of the patients was 65.4±6.45 years with mean BMI 27.3±4.67 kg/m2. Tobacco smoking was found in 151 (60.4%) among. Frequency of diabetes was found among 80 (28%) cases. Among 80 cases of diabetes, 72 (90%) patients had recent onset diabetes. Mean age of diabetes diagnose was 56.34±5.34 years and mean age of pancreatic cancer diagnosed was 58.9±6.77 years. Head in pancreas was the most common affected side of tumor among 58 (72.5%), followed by body 12 (15%) and tail in 10 (12.5%) cases. Conclusion: In this study we concluded that frequency of diabetes among pancreatic cancer patients was 28% and majority of the cases had new-onset diabetes. Except this tobacco smoking was significant causing factor for pancreatic cancer. It may be possible to screen for pancreatic cancer in new-onset diabetes by identifying a particular biomarker for pancreatic cancer.